Support for Asynchronous Interaction in Group Experiential Learning - Meloche, Joseph; Hasan, Helen; Papakosmas, Angelo (Outlines. Critical Practice Studies, 2004)
<span style="font-family: Times; font-size: 12pt; mso-ansi-language: EN-AU; mso-fareast-font-family: Times New Roman; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: Times New Roman;" lang="EN-AU">To be relevant to the constantly changing work patterns of the real world, effective learning in universities often occurs in small groups facilitated by collaborative environments where participants are dynamically involved in purposeful activities. The research described in this paper is an investigation of purposeful group work devised for experiential learning where a variety of socio-technical tools were used to support asynchronous tasks and communication among the learners. In order to explore the complexity of this collaborative activity a distinctive inductive research approach has been adopted using reflective developmental methods. The data collection and the analysis part of the research involved the reflection of participants on their activity being requested as reports within their course work. Student reports were subject to content analysis using a computer-based tool that creates a conceptual map of collections of documents comparing the ratings and relationships of concepts among different sets of participants. The study was enhanced by the use of Q-methodology that allows the participants to outline their views and to make individual decisions on the relative importance that they place upon the available views of the larger group. Concepts from Activity Theory allowed the researchers to take a holistic contextual approach both to the design of the research and the interpretation of the findings to make some sense of the complexity of the dynamic work-learning dialectic in a socio-technical collaborative setting.